IMPACT OF ISRADIPINE AS A CALCIUM ANTAGONIST ON ERYTHROPOIETIN, SERUM CALCIUM, AND LUNG FUNCTION IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Dr. Syeda Masooma Hussain; Dr. Tahira Jehangir; Dr. Ghazan Askar; Dr. Zara Khalid Khan; Dr. Danyal Khattak; Dr. Ayesha Jamil (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Chronic obstructive pulmonary disease (COPD) poses a global health threat, marked by progressive lung function decline and airflow restriction. Erythropoietin (EPO), traditionally associated with hematopoiesis, emerges as a focal point in COPD pathophysiology.Objective: The study aimed to investigate the interplay between lung function, serum calcium concentrations, and erythropoietin levels in chronic obstructive pulmonary disease (COPD) patients, with a focus on assessing the potential therapeutic advantages of isradipine, a calcium antagonist.Methodology: The research design integrates cross-sectional observational, 138 COPD-diagnosed individuals were recruited. from diverse healthcare settings. The comprehensive sample collection involved interviews, spirometry assessments, and a 12-week intervention with isradipine or a placebo. Statistical analyses, including descriptive statistics, ANOVA, t-tests, and regression, provided a detailed exploration of these complex relationships.Results: Smoking, a prevalent COPD risk factor, was noted in over half of the participants. Lung function measures exhibited a substantial decline with increasing COPD severity, particularly in FEV1 and FVC. Isradipine treatment showed a non-significant increase in FEV1 (2.5 to 2.8 liters) and a statistically significant improvement in FVC (3.0 to 3.2 liters) after 12 weeks. Regression analysis unveiled a noteworthy association between elevated blood calcium levels and improved predicted FEV1 (β = 0.25, p = 0.002). Conversely, higher serum erythropoietin levels (β = -0.15, p = 0.011) and escalating COPD severity (β = -0.4, p < 0.001) were linked to diminished predicted FEV1, underscoring their adverse impact on lung function.Conclusion: Our study highlights the intricate relationships among serum calcium, erythropoietin, and lung function in COPD, offering insights for personalized treatment approaches and future investigations.